RANCANGAN APLIKASI ABSENSI SISWA BERBASIS WEB PADA SMK SMAK PADANG: DESIGN OF A WEB-BASED STUDENT ATTENDANCE APPLICATION AT SMAK PADANG VOCATIONAL SCHOOL - Dahri , Nuraeni; Hermanto, Erit (Jurnal Manajemen Teknologi Informatika, 2024)
The design of a web-based filing system at SMK SMAK Padang aims to overcome the problem of an ineffective and efficient filing system at SMK SMAK Padang. The process of controlling the filing system that runs at SMK SMAK Padang is still done manually. This can slow down the search process for letter archives at the school. The system design in this Final Project (TA) was built using a website platform and run online. The research method uses the System Development Life Cycle (SDLC). System design tools use the Unified Modeling Language (UML) method using 4 design diagrams namely Usecase Diagrams, Sequence Daigrams, Activity Diagrams and Class Diagrams.